Application of the Principle of Mutual Consent in Consular Relations between States: Array - Maftei, Jana (Acta Universitatis Danubius. Juridica, 2020)
The pursuit of consular activity by one state on the territory of another state affects the sovereignty of the latter. In the spirit of respect for state sovereignty, the establishment and conduct of consular relations, a separate category of international relations, part of all relations governed by international law, are subject to the principle of mutual consent of states involved in consular relations. This study focuses in particular on the analysis of the application of the principle of mutual consent to the establishment and maintenance of consular relations, the establishment of consular offices, the appointment and admission of members of the consular office and the exercise of consular functions, from the perspective of the 1963 Vienna Convention to consular relations. We will emphasize the special importance and indispensable nature of this principle for states wishing to maintain consular relations, in close correlation and in the light of the principle of sovereign equality of states. For the elaboration of the paper we have used as research methods the analysis of the problems generated by the mentioned subject with regard to the doctrinal views expressed in the treaties and papers, the documentary research, the interpretation of legal norms in the matter.